1997
DOI: 10.1007/s002669900153
|View full text |Cite
|
Sign up to set email alerts
|

Successful Surgery of Multiple Recurrent Basal Cell Carcinomas Guided by Photodynamic Diagnosis

Abstract: We describe a 56-year-old Caucasian man with history of multiple regressed basal cell carcinomas. During the last 20 years approximately 200 histologically proven basal cell carcinomas preferentially localized on the face were surgically treated. Several large skin grafts were necessary to cover the extensive tissue defects on the face and scalp. Although all excised tissues were histologically proven to be basal cell carcinomas with tumor-free margins, new tumors developed in proximity to the skin graft margi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
3

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 8 publications
0
20
0
3
Order By: Relevance
“…6 Therefore, PDT coupled with ALA is used not only for treatment but also for diagnosis. 6,8 This treatment is also effective for benign cutaneous disorders. 4,6,9 Concerning the influence of ALA-PDT on sebaceous glands and hair follicles, Divaris et al 3 reported an in vivo study in albino mice.…”
Section: Commentmentioning
confidence: 99%
“…6 Therefore, PDT coupled with ALA is used not only for treatment but also for diagnosis. 6,8 This treatment is also effective for benign cutaneous disorders. 4,6,9 Concerning the influence of ALA-PDT on sebaceous glands and hair follicles, Divaris et al 3 reported an in vivo study in albino mice.…”
Section: Commentmentioning
confidence: 99%
“…While the emission spectrum of autofluorescence is in the green spectrum, the emission spectrum of ALA/MAL is in the red range. The advantage of the use of autofluorescence in cancer demarcation is that there is no need to apply exogenous substances, which may be time-consuming and potentially harmful [15,16,17,18].…”
Section: Digital Imagingmentioning
confidence: 99%
“…This type of clinical application has been widely reported in literature [8][9][10]. This is possible because the photosensitizer molecules have higher affinity to cancer cells compared to normal cells.…”
Section: Introductionmentioning
confidence: 99%